Student Talent Project Strengthens Madrasah Students Soft Skills: Proyek Bakat Siswa Menguatkan Soft Skill Siswa Madrasah - Lutfiah, Dwi Nur; Nurmawati, Nurmawati (Pedagogia : Jurnal Pendidikan, 2026)
This study outlines the General Background that education in the disruption era requires systematic soft skill formation alongside academic learning, particularly in Islamic schools emphasizing character development. The Specific Background focuses on the Student Talent Project (Proyek Bakat Siswa/PBS) implemented at Madrasah Aliyah An-Nur Prima Medan through Fardhu Kifayah, Calligraphy, Arabic Class, Silat, and Archery. The Knowledge Gap concerns the limited research explicitly examining PBS activities, student experiences, developed soft skills, and determining factors within this madrasah context. The Aims are to analyze the role of PBS in developing students’ soft skills and to identify factors influencing its implementation using a descriptive qualitative approach with interviews, observation, documentation, and interactive data analysis. The Results show that PBS fosters communication, teamwork, leadership, creativity, responsibility, and discipline, supported by mentor competence, student motivation, institutional facilities, religious culture, consistent implementation, and evaluation systems. The Novelty lies in its integrated analysis of PBS programs, student experiences, specific soft skill outcomes, and contextual determinants within one Islamic senior high school. The Implications indicate that structured religious extracurricular programs can serve as practical platforms for holistic soft skill and character formation in madrasah education. Highlights• Structured religious extracurricular activities cultivate interpersonal and social competencies among participants.• Experiential and project-based practices foster leadership, collaboration, and self-regulation.• Mentor quality, institutional support, and consistent scheduling determine program sustainability. KeywordsStudent Talent Project; Soft Skills Development; Islamic Education; Extracurricular Activities; Experiential Learning